Discourse Theory and Critical Media Politics
IX, 257 p.
Keywords: A systematic examination of the relationship between post-Marxist discourse theory and media studies. This volume interrogates discourse theory – as read via the work of Ernesto Laclau and Chantal Mouffe – through an engagement with major approaches to critical media politics and a range of issues in contemporary media politics.